FDI Prospects and Challenges Ahead for India - Aluvala, Ravi (Indian Journal of Finance, 2011)
One of the most notable features of economic globalization has been the increased importance of foreign direct investment around the world. Some view it as an engine of economic growth and development, while others look upon it as a panacea for all ills. It is, however, important to weigh the costs and the benefits of Foreign Direct Investment (FDI) to gauge whether FDI has a positive impact on economic development. FDI has the potential to generate employment, raise productivity, enhancing competitiveness of the domestic economy through transfer skills and technology, strengthening infrastructure, enhance exports and contribute to the long-term economic development of the world's developing countries. More than ever, countries at all levels of development seek to leverage FDI for development. We, in India, see FDI as a developmental tool in all sectors and tourism has no exceptions. Liberalization policies have led to rapid growth in FDI inflows in recent years. Based on the benefits associated with FDI, several developing; as well developed countries compete fiercely for FDI. They try to attract foreign investors by providing financial and fiscal incentives, undertaking corporate restructuring and economic reforms and inviting foreign investors in the privatization of state-run units. In 2001, for example, 71 countries made 208 changes in their FDI regulatory regimes, out of which 194 had done the same to attract higher FDI. The global market for foreign direct investment (FDI) has undergone significant changes in recent years, with the increasingly important role played by emerging market multinational enterprises (MNEs) being one of the most important ones among them. While outward FDI (OFDI) from these countries, in itself, is not new, the magnitude that this development has achieved, is raising a host of issues that are examined in this paper. The rise of global OFDI over the past three decades has been remarkable. Since 1980- 1985, when global OFDI flows averaged roughly US$50 billion per year, OFDI flows have grown by a factor of forty, to surpass US$2.1 trillion in 2007. In 2008, due to the financial crisis and the global economic downturn, global OFDI flows fell by roughly 10% to US$1.9 trillion.